Genetic Diversity of Red Rice (Oryza Sativa L.) Population M2 Results of G16 Rice Genotype Mutations with 200gy and 300gy Gamma Ray Iradiation - A A K Sudharmawan; I G P M Aryana; Ni Wayan Sri Suliartini; Sofian Aji Purnama (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2022)
Mutational breeding can be used to obtain superior varieties by improving some of the desired traits, without changing most of the good traits. The purpose of this study was to determine the genetic diversity of brown rice through segregation of traits in rice mutants due to gamma ray irradiation at doses of 200 gy and 300 gy. The method used is an experimental method carried out from May to September 2021 with a single plant. The distribution of the data was tested by the Kolmogorov-Smirnov test using software and the segregation ratio suitability test using the Chi-Square method with a 5% significance level. The results showed that the data distribution was normally distributed, meaning that it was controlled by many genes (polygenic). on the quantitative trait whose data distribution is not normally distributed, it indicates that the trait is controlled by simplegenic. The results of the Mendel's ratio suitability test using Chi-Square for quantitative traits that follow the Mendelian ratio, which shows a segregation ratio of 9: 7 (double recessive epistasis) where the same phenotype is produced by both homozygous recessive genotypes and two recessive genes are epistatic to the dominant allele. For traits that do not follow the Mendelian ratio or their modifications, it is assumed that they are controlled by many genes (minor genes) so that individual effects are difficult to distinguish.